Coherent imaging at the Diamond beamline I13 - Rau, Christoph; Wagner, Ulrich; Pešić, Zoran; De Fanis, Alberto (Physica status solidi. A, Applications and materials science, 2011)
The Diamond beamline I13 for imaging and coherence applications is dedicated to hard X‐ray imaging on the micro and nano‐lengthscale. Two independent stations will be operated in a separate building at a distance of 250 m from the source. The imaging branch will perform in‐line phase contrast imaging and tomography over a large field of view in the 6–35 keV energy range. In addition it will be possible to switch to full‐field microscopy with 50 nm spatial resolution. Other microscopies will be developed according to the scientific needs. Resolution beyond the limitations given by the detector and X‐ray optics will be achieved on the ‘coherence’ branch. Techniques working in the far field such as Coherent X‐Ray Diffraction and other Coherent Diffraction Imaging techniques such as ptychography will be implemented. Typical applications cover different fields such as bio‐medicine, materials science, geo‐ and astrophysics or even cultural heritage. The beamline hosts a number of innovative features such as the so‐called ‘mini‐beta’ layout for electron optics in the storage ring or new concepts for beamline instrumentation. The stations will be operational in 2011.